“A Red Snake in Paraná”: The Intervention of the Revolutionary Workers Party-People's Revolutionary Army in the Struggle of the Metallurgical Workers of Villa Constitución (1974-1975) (Palimpsesto, 2022)
The struggle of the metallurgical workers of Villa Constitución during the years 1974 and 1975 was one of the highest points of the workers' conflict in the Argentine 70s. His levels of mobilization and radicalism transformed him into a political problem for the Peronist government and a challenge for the revolutionary organizations that participated within it. In this article we seek to reconstruct the intervention of one of the organizations that acquired greater prominence in that conflict: the Workers' Revolutionary Party - People's Revolutionary Army. Specifically, we analyze the characteristics of their organization and the effects, debates and tensions of their commitment to link guerrilla action with the union struggle.
Keywords: PRT-ERP; Villa Constitución; Armed struggle; Union struggle; Villazo